Effects of Curcumin on Stability and Efficacy of Neem Leaves Extract as Botanical Insecticides - Elika Joeniarti; Masfufatun Masfufatun; Noer Kumala Indahsari; Endang Noerhartati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Botanical insecticides are considered biodegradable, environmentally compatible, and less toxic to non-target organisms than synthetic insecticides. Unfortunately, they are not attractive to Indonesian farmers due to its instability against light, temperature, and microbes, as well as they, have short storage time. This research was intended to produce a distinctive botanical insecticide that is resilient against the light, microbes, and durable. The role of curcumin in the stability and efficacy of neem (Azadirachta indica) leaves extract as a botanical insecticide against soybean pod sucking bug, Riptortus linearis was evaluated in the laboratory. This research was conducted at the Organic Chemistry Laboratory of Chemistry Department, Faculty of Science and Technology Airlangga University and the Plant Protection Laboratory, Faculty of Agriculture University of Wijaya Kusuma Surabaya, Indonesia, from March to October 2016. The results explained that curcumin is no effect on increase the stability of neem leaves extract solution towards UV light irradiation. However, it can increase the insecticide activity of neem leaves extract solution up to 96% mortality against soybean pod sucking bug, R. linearis. The increase of the bioactivity refers to the anti insecticidal activity of ferulic acid formed from the degradation of curcumin.